Alternative models for academic family practices - Yarnall Kimberly SH; Krause Katrina M; Kaprielian Victoria S; Østbye Truls; Michener J; Yaggy Susan D; Gradison Margaret (BMC, 2006)
Abstract Background The Future of Family Medicine Report calls for a fundamental redesign of the American family physician workplace. At the same time, academic family practices are under economic pressure. Most family medicine departments do not have self-supporting practices, but seek support from specialty colleagues or hospital practice plans. Alternative models for academic family practices that are economically viable and consistent with the principles of family medicine are needed. This article presents several "experiments" to address these challenges. Methods The basis of comparison is a traditional academic family medicine center. Apart of the faculty practice plan, our center consistently operated at a deficit despite high productivity. A number of different practice types and alternative models of service delivery were therefore developed and tested. They ranged from a multi-specialty office arrangement, to a community clinic operated as part of a federally-qualified health center, to a team of providers based in and providing care for residents of an elderly public housing project. Financial comparisons using consistent accounting across models are provided. Results Academic family practices can, at least in some settings, operate without subsidy while providing continuity of care to a broad segment of the community. The prerequisites are that the clinicians must see patients efficiently, and be able to bill appropriately for their payer mix. Conclusion Experimenting within academic practice structure and organization is worthwhile, and can result in economically viable alternatives to traditional models.